2019
DOI: 10.1111/jfbc.13126
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antihypertensive effects of garlic protein and its hydrolysates and the related mechanism

Abstract: Garlic protein (GP) was enzymatically hydrolyzed using pepsin and trypsin followed by the evaluation of antioxidant and angiotensin-converting enzyme (ACE) inhibitory activities of GP and its hydrolysates. The antihypertensive effects of GP and its hydrolysates were determined in vivo. The results showed that GP and its hydrolysates namely GPH-P (pepsin) and GPH-T (trypsin) possessed appreciable antioxidant and ACE inhibitory activities. The ACE inhibitory activity of GP, GPH-T, and GPH-P was in consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In addition, this effect was long lasting, remaining until 48 h post administration. A similar time response of the SBP-lowering effect has been shown by hydrolysates obtained from other food by-products such as garlic protein hydrolysates, which exhibited the maximum effect between 4-6 h post-administration [60]. It is noteworthy that, since it lasted longer, the antihypertensive effect of the PWL was more potent than the one shown by the commercially available drug Captopril or the 0 WL.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, this effect was long lasting, remaining until 48 h post administration. A similar time response of the SBP-lowering effect has been shown by hydrolysates obtained from other food by-products such as garlic protein hydrolysates, which exhibited the maximum effect between 4-6 h post-administration [60]. It is noteworthy that, since it lasted longer, the antihypertensive effect of the PWL was more potent than the one shown by the commercially available drug Captopril or the 0 WL.…”
Section: Discussionsupporting
confidence: 69%
“…ACE-inhibitory peptides have been reported from various enzymatic food protein hydrolyzates such as canola (Alashi et al, 2014), oat (Bleakley, Hayes, O'Shea, Gallagher, & Lafarga, 2017), wheat bran (Zou, Wang, Wang, Aluko, & He, 2020), peanut (Gong et al, 2017), and rice (Pinciroli, Aphalo, Nardo, Añón, & Quiroga, 2019). The damaging effects of oxidative stress on the human body and the relationships to chronic diseases like diabetes, obesity, and hypertension have been well documented (Fang et al, 2019;Faraone et al, 2019;Gao et al, 2020). Therefore, the use of multifunctional peptides with inhibitory activities against α-amylase, α-glucosidase, ACE, and toxic free radicals could enable prevention and treatment of diabetes, obesity, and hypertension (Chatchaporn & Jian, 2016;Meshginfar, Mahoonak, Hosseinian, & Tsopmo, 2019).…”
mentioning
confidence: 99%
“…In 2015, Magaña et al [ 46 ] obtained hydrolysates from Phaseolus lunatus and some fractions had inhibition percentage above 50% and reported IC50 values in the range of 0.9 to 3.8 µg/mL, Daliri et al [ 47 ] report 88% of ACE inhibition and IC50 of 0.59 mg/mL from soy protein hydrolysates. Garlic protein hydrolysates reported by Gao et al [ 48 ] have IC50 of 0.89 mg/mL; finally, in 2020, Suwannapan et al [ 49 ] studied the effect of SGID on the ACEI activity of rice protein, finding that ACE inhibition does not reach 30%. None of these studies reached the percentage of inhibition or IC50 found for the CNV44 hydrolysate, except for the report by Magaña; however, in the present work, we tested the complete hydrolysates and not fractions as Magaña et al…”
Section: Discussionmentioning
confidence: 99%